BLACK WOMEN'S AGING AND NEUROPSYCHOPEDAGOGY: INTERSECTIONAL CHALLENGES AND STRATEGIES FOR QUALITY OF LIFE - Lisboa, Cristiane Almeida; de Souza Junior, Antonio Cordeiro (Seven Editora, 2026)
This article explores the accelerated aging of the Brazilian population, focusing on the challenges faced by Black women, a vulnerable group due to structural racism, gender inequality, and socioeconomic conditions. These women experience cumulative exclusion that affects their health, well-being, access to rights, and learning capacity. The objective is to analyze the relationship between the aging of Black women and the contributions of neuropsychopedagogy to promoting quality of life, autonomy, and learning in this group. To this end, a qualitative, descriptive, and analytical approach is used, grounded in bibliographical research. Thus, it is observed that neuropsychopedagogy emerges as an essential field, articulating knowledge from neuroscience, psychology, and pedagogy to understand aging as a dynamic and continuous learning process, valuing brain plasticity and sociocultural experiences. The study highlights the importance of neuropsychopedagogical interventions based on the valorization of these women's identity, culture, and traditional knowledge, promoting self-esteem, belonging, and social participation, despite access barriers such as socioeconomic inequalities and Eurocentric models. It is concluded that a critical and intersectional neuropsychopedagogy is crucial for promoting equity, dignity, and quality of life for Black women in old age, reaffirming learning as an inalienable right throughout life.DOI: https://doi.org/10.56238/sevened2026.008-038